2008
DOI: 10.1093/annonc/mdn043
|View full text |Cite
|
Sign up to set email alerts
|

Can dynamic contrast-enhanced MRI (DCE-MRI) predict tumor recurrence and lymph node status in patients with breast cancer?

Abstract: The lymph node status is regarded as one of the most important prognostic factors for the overall and disease-free survival of patients with breast cancer. While morphological features and contrast enhancement kinetics of breast cancer shown on dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) have been correlated with tumor histological type, grade, and biomarkers [1][2][3][4], there were only few studies reporting the association of lesion features such as rim enhancement and kinetic feature (ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…However, two other studies did not find a correlation between ANS and early-phase kinetics (9, 29). Bahri et al (29) observed significant differences in delayed-phase kinetic characteristics between node-positive and node-negative patients, although our measure of delayed-phase kinetics (WE) was not correlated with ANS. Altogether, findings from previous studies examining DCE-MRI kinetic parameters with regard to nodal status have been mixed, although their techniques have varied with respect to examination protocols and definitions of kinetic parameters, making comparisons challenging.…”
Section: Discussioncontrasting
confidence: 60%
“…However, two other studies did not find a correlation between ANS and early-phase kinetics (9, 29). Bahri et al (29) observed significant differences in delayed-phase kinetic characteristics between node-positive and node-negative patients, although our measure of delayed-phase kinetics (WE) was not correlated with ANS. Altogether, findings from previous studies examining DCE-MRI kinetic parameters with regard to nodal status have been mixed, although their techniques have varied with respect to examination protocols and definitions of kinetic parameters, making comparisons challenging.…”
Section: Discussioncontrasting
confidence: 60%
“…Currently, the correlation between DCE-MRI quantitative parameters and prognosis factors of breast cancer, including enhanced morphology, tumor size, pathological grade, and lymph node status, is still in the preliminary stage, and the results of different studies are quite different [23, 24]. Koo et al investigated the correlations between parameters (Ktrans, Kep, and Ve) of 70 IDCs and tumor size [23].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also showed that Ktrans has significant positive correlation with LNM, while only Ve values exhibit significant difference between subgroups of LN, which is firstly reported in this study to date. Bahri et al reported that LN(+) group has higher Kep than the LN(−) group [24]. The inconsistent results may be due to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that pharmacokinetic parameters can potentially be used as prognostic or predictive biomarkers [ 13 ]. Bahri et al [ 14 ] found that the Ktrans and Ke p values of metastatic lymph nodes are higher than those of nonmetastatic lymph nodes in breast cancer. However, using combined pharmacokinetic parameters and DCE-MRI radiomics features to predict SLN metastasis has not yet been demonstrated.…”
Section: Introductionmentioning
confidence: 99%